2009
DOI: 10.4028/www.scientific.net/jbbte.3.25
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Alginate/Poly(L-Arginine)-Chitosan Ternary Complex Microcapsules

Abstract: Following a polyelectrolytical complex reaction, alginate/poly(L-Arginine)-chitosan ternary complex microcapsules were prepared by coating poly(L-Arginine) and chitosan as membrane materials on calcium alginate beads, which were produced by a high-voltage electrostatic droplet generator. The influences on the diameter and uniformity of the calcium alginate beads were studied, and the optimum operating parameters were selected to produce microcapsules. The in vitro drug release behavior and pH stimuli-response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…5 has shown the release profile of indomethacin in pH 2.1, 7.4 PBS at 37 o C. It was found that only 22.3 % of indomethacin was released from the beads at pH=2.1 PBS, whereas 60.1 % indomethacin was diffused into pH=7.4 PBS within 500 mins. The same tendency of drug release in different pH PBS was also reported in other drug release system composed of alginate/poly(L-arginine)-chitosan microcapsules [7] and N-carboxymethyl chitosan beads [8]. In pH=2.1 PBS, the ionization of carboxyl groups is very low, so the H-bonding among polymeric network derived from NH and COOH groups was very strong.…”
supporting
confidence: 74%
“…5 has shown the release profile of indomethacin in pH 2.1, 7.4 PBS at 37 o C. It was found that only 22.3 % of indomethacin was released from the beads at pH=2.1 PBS, whereas 60.1 % indomethacin was diffused into pH=7.4 PBS within 500 mins. The same tendency of drug release in different pH PBS was also reported in other drug release system composed of alginate/poly(L-arginine)-chitosan microcapsules [7] and N-carboxymethyl chitosan beads [8]. In pH=2.1 PBS, the ionization of carboxyl groups is very low, so the H-bonding among polymeric network derived from NH and COOH groups was very strong.…”
supporting
confidence: 74%
“…The expected strong nuclear uptake of pArg containing SmacN7 conjugate mediated cell death in tumor and healthy cells [96]. Ternary complex microcapsules of alginate/pArg-chitosan were fabricated by coating chitosan and pArg as membrane materials on calcium alginate beads [97]. The investigation of the in vitro drug release alginate/pArg-chitosan microcapsules exhibit more sustained and stable macromolecular drug release compared with alginate/chitosan microcapsules.…”
Section: Types Of Ph-responsive Polypeptidesmentioning
confidence: 99%
“…Ponce's results [3] illustrate that the different observed immune responses to alginate microcapsules are the consequence of the variations in the interactions between the polycations and alginates rather than to the alginates themselves. At present, chitosan and poly-L-lysine (PLL) are widely used as polycationic coating materials for polyelectrolytical complex reactions [4][5][6][7][8]. However, a perfect encapsulation system requires a gel entrapment system which is chemically and mechanically stable as well as biocompatible both for the host and the entrapped cells [3,9], and some reports show that the mechanical strength and biocompatibility of PLL microcapsules need to be improved [7,8].…”
Section: Introductionmentioning
confidence: 99%